Analysis of the atomization performance of hydrodynamic rotating spray dust suppression device with setting fan - Hui XU; Qinghua CHEN; Dejun WANG (Meikuang Anquan)
In recent years, with the significant improvement of mechanization and intelligence in coal mining in China, the amount of dust produced during working face operations has increased significantly, and higher requirements have been put forward for dust control technology. In order to study the influence of setting fans on the atomization performance of hydrodynamic rotating spray dust suppression device, based on the hydrodynamic driving rotating spray dust suppression device, the influence of key structural parameters of the water shaft on the speed was explored, and a three-dimensional flow field model was established using dynamic grid technology to analyze the influence of the angle of water flow, the angle of concentration, and the water supply pressure on the speed of the water shaft; we construct a VOF multiphase flow model and compare the velocity distribution characteristics of the mixed outlet fog particle field at different water axis outlet angles of 15°-75°; the structure of the device is improved. Because the device is not driven by electricity, the volume and weight of the device are greatly reduced. At the same time, the fan blade is set on the water shaft, so that the device has both rotating spray and negative pressure suction dust reduction functions; we build a coal mine dust experimental system, collect coal dust samples from Inner Mongolia 5013 excavation face, and measure the total dust and respiratory dust concentrations of three dust reduction schemes through CCZ-20A dust sampler. The results showed that among the key structural parameters of the water shaft, the angle of water flow and the angle of concentration had a relatively small effect on the rotational speed, with a maximum relative deviation of only 2.91%. However, the water supply pressure was significantly positively correlated with the rotational speed, with a rotational speed of 1 448.6 rpm at 4 MPa, an increase of 32.6% compared to 2 MPa; after the integration of fan blades, the atomization performance is optimal when the water axis outlet angle is 30°. The axial velocity of the mixing outlet reaches 39.2 m/s and the distribution uniformity is improved by 42%. At the same time, a stable negative pressure suction flow field of 5.5 m/s is formed. Field experiments show that the new device makes the total dust reduction rate rise to 91.3%, 17.7% higher than that of the device without fan blades; the respirable dust reduction rate reaches 51.9%, 129% higher than that of the conventional spray scheme.